The Effect of Budget Participation and Leadership Style on Regional Budget Performance: The Moderating Role of Accountability in the Semarang City Government - Haryanda, Feren; Rohman, Abdul (Dinasti Publisher, 2025)
This study examines the influence of budget participation and leadership style on regional budget performance, with accountability as a moderating variable in the Semarang City Government. The results indicate that budget participation has a positive and significant effect on budget performance. Greater employee involvement in the budgeting process leads to improved performance by fostering a sense of ownership and responsibility, which enhances budget efficiency and effectiveness. Leadership style also positively and significantly influences budget performance, particularly transformational and collaborative leadership that provides vision, motivation, and active engagement in financial management. Furthermore, accountability moderates the relationship between budget participation and budget performance, strengthening the positive impact when a transparent and firm accountability system is in place. Similarly, accountability moderates the effect of leadership style on budget performance. The presence of a strong culture of accountability enhances the role of leadership in achieving budget targets, acting as a catalyst within the regional government bureaucracy.